The Kingfisher student atlas. - Anderson Geographics Limited (Boston, MA : Kingfisher, 2003)
An atlas of physical and political maps of the world, organized by continent, plus fact boxes containing statistics about the land and people of each place.
Includes glossary and index.
"Maps designed and produced by Anderson Geographics Limited, Warfield, Berkshire, England"-- Prelim. p. [2].
Accompanying CD-ROM titled: Kingfisher student atlas classed under G3200 2003 .K8 CD.
System requirements for accompaning CD-ROM: IBM PC and Mcintosh.
Keywords: Children's atlases; Atlases; Atlases